SHALAT KESELARASAN SEMESTA: Keterhubungan Hukum Hakikat dan Hukum Syariat - Mohamad Mahrusillah; Abusiri Abusiri (STAI ALHIKMAH Jakarta, 2022)
AbstractThis article aims to explore the cohesion and harmony of the meaning of prayer that connects the law of occurrence (essence) and the law of brushing (Shari'a) as the main capital of the progress of one nation's civilization. This study uses a linguistic approach that is analyzed linguistically by researchers and literature study. From the results of the analysis and study of the author, it was found that individuals who halt their lives by interpreting the concept of 3 (three) pillars of prayer will harmonize the law of their essence and the law of the rule of worship against themselves. The pattern of harmony between the laws of nature and the laws of collective Sharia will build prosperity for mankind, and will give birth to blessings in the form of prosperity and progress of one nation's civilization. AbstrakArtikel ini bertujuan untuk menggali kohesi dan harmoni pemaknaan shalat yang menghubungkan hukum kejadian (hakikat) dan hukum penyikapan (syariat) sebagai modal utama kemajuan peradaban satu bangsa. Kajian ini menggunakan pendekatan linguistik yang dianalisa secara kebahasaan oleh peneliti dan pendekatan studi literatur. Dari hasil analisa dan kajian penulis ditemukan bahwa individu yang menshalatkan kehidupannya dengan memaknai konsep 3 (tiga) rukun shalat akan menyelaraskan hukum hakikat dirinya dan hukum aturan penyikapan terhadap diri. Pola keselarasan hukum hakikat dan hukum syariat kolektif akan terbangun kesejahteraan untuk umat manusia, serta akan melahirkan keberkahan berupa kemakmuran dan kemajuan peradaban satu bangsa.